2012
DOI: 10.1021/jp3072684
|View full text |Cite
|
Sign up to set email alerts
|

Diradical Character Based Design for Singlet Fission of Condensed-Ring Systems with 4nπ Electrons

Abstract: By applying the diradical character based molecular design guideline for singlet fission (SF), we investigate the feasibility of efficient SF in condensed-ring π-conjugated molecules with 4nπ electrons (n = 4, 5, ...), i.e., antiaromatic polycyclic hydrocarbons composed of fiveand sixmembered rings. The multiple diradical character (y i ), which takes a value between 0 (closed shell) and 1 (pure open shell), is defined as the occupation number of the lowest unoccupied natural orbital (LUNO) + i (i = 0, 1, ...)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 75 publications
6
99
0
Order By: Relevance
“…As other examples of diradical‐character‐based design for singlet fission molecules, Ito and I investigated antiaromatic polycyclic hydrocarbons with 4 n π electrons ( n =4, 5, etc.) composed of five‐ and six‐membered rings (Figure ) and several heteroacene models involving nitrogen (N) atoms (Figure ) . For the antiaromatic PAHs, we evaluated the excitation energies at the TD‐tuned‐LC–DFT level of theory with the Tamm–Dancoff approximation, and then found that the energy level matching conditions are satisfied in relatively small‐sized antiaromatic condensed‐ring molecules with y 0 ∼ 0.4 and y 1 / y 0 < 0.2, i. e., intermediate diradical character without significant tetraradical character [indenofluorene‐like molecules 2 (2) and 2 (3)].…”
Section: Open‐shell‐character‐based Design Principle For Efficient Simentioning
confidence: 99%
“…As other examples of diradical‐character‐based design for singlet fission molecules, Ito and I investigated antiaromatic polycyclic hydrocarbons with 4 n π electrons ( n =4, 5, etc.) composed of five‐ and six‐membered rings (Figure ) and several heteroacene models involving nitrogen (N) atoms (Figure ) . For the antiaromatic PAHs, we evaluated the excitation energies at the TD‐tuned‐LC–DFT level of theory with the Tamm–Dancoff approximation, and then found that the energy level matching conditions are satisfied in relatively small‐sized antiaromatic condensed‐ring molecules with y 0 ∼ 0.4 and y 1 / y 0 < 0.2, i. e., intermediate diradical character without significant tetraradical character [indenofluorene‐like molecules 2 (2) and 2 (3)].…”
Section: Open‐shell‐character‐based Design Principle For Efficient Simentioning
confidence: 99%
“…Intriguingly, these compounds have been found to be non-emissive and thus we wished to examine their photophysics. One possible mechanism for non-emissive relaxation from a photoexcited state to the ground state is singlet fission, proposed to be present in the expanded system fluorenofluorene (1), due to ideal state energies for singlet fission [18]. This process is particularly desirable in OPVs as it may boost the maximum power conversion efficiency and impede loss pathways from charge recombination [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Since the indenofluorene derivatives include a p -quinodimethane core, it is known that these molecules show biradical character originating from the aromatization of the central benzene ring 53 . Thus, the singlet biradical characters ( y ) of 2(Me) and IF were estimated using the occupation numbers of the spin-unrestricted Hartree–Fock natural orbitals.…”
Section: Resultsmentioning
confidence: 99%